Energy minimization methods in computer vision and pattern recognition: 10th international conference, EMMCVPR 2015, Hong Kong, China, January 13 - 16, 2015 ; proceedings - Tai, Xue-Cheng (Lecture notes in computer science, 2015)
Discrete and continuous optimization -- Image restoration and inpainting -- Segmentation -- PDE and variational methods -- Motion, tracking and multiview reconstruction -- Statistical methods and learning -- Medical image analysis.
Literaturangaben
Gesehen am 30.07.2018
Keywords: Konferenzschrift -- 13.01.2015-16.01.2015 -- Hong Kong; Optimierung; Mustererkennung; Maschinelles Sehen